2010
DOI: 10.1021/je1008137
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Density of Five Hydrocarbon Liquids at Pressures up to 200 MPa and Temperatures up to 473 K

Abstract: We report the results of simultaneous measurements of the viscosity and density of five pure hydrocarbon liquids (octane, decane, 1,3-dimethylbenzene, 1,2,3,4-tetrahydronaphthalene and 1-methylnaphthalene) at temperatures between 298.15 K and 473.15 K and at pressures ranging from 0.1 MPa to approximately 200 MPa. The measurements were made with a vibrating-wire instrument and the estimated expanded relative uncertainties are ±2 % for viscosity and ±0.2 % for density with a coverage factor of 2. The densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(62 citation statements)
references
References 0 publications
9
53
0
Order By: Relevance
“…From these deviations, we can also conclude that the experimental data are internally consistent to within the estimate experimental uncertainty. Equation (16) Figure 7, we compare the new results with data from the literature [13][14][15][16][17][18][19] at pressures up to 10 MPa as deviations from the correlation of Tariq et al 1 Our results agree well with the majority of the experimental data reported in the literature; however, the data of Rajagapol et al 17 at temperatures below 400 K and those of Grachev et al 19 to constrain the behavior of their correlation in the liquid state at temperatures above 441 K and those data are systematically higher than ours at temperatures above 450 K. Figure 8 compares our new results with data from the literature 13,14,[20][21][22][23][24][25][26][27][28][29] at pressure up to 10 MPa as deviations from the correlation of Huber et al 2,3 At temperatures up to 500 K, our new data agree with the correlation to within about ±1 %, which is the stated uncertainty of the correlation for the saturated liquid. At higher temperatures, the deviations are somewhat dependent upon pressure and span the interval (-3 to -6) %.…”
Section: Correlation Of the Viscosity Ratios At Low Temperatures Thsupporting
confidence: 90%
“…From these deviations, we can also conclude that the experimental data are internally consistent to within the estimate experimental uncertainty. Equation (16) Figure 7, we compare the new results with data from the literature [13][14][15][16][17][18][19] at pressures up to 10 MPa as deviations from the correlation of Tariq et al 1 Our results agree well with the majority of the experimental data reported in the literature; however, the data of Rajagapol et al 17 at temperatures below 400 K and those of Grachev et al 19 to constrain the behavior of their correlation in the liquid state at temperatures above 441 K and those data are systematically higher than ours at temperatures above 450 K. Figure 8 compares our new results with data from the literature 13,14,[20][21][22][23][24][25][26][27][28][29] at pressure up to 10 MPa as deviations from the correlation of Huber et al 2,3 At temperatures up to 500 K, our new data agree with the correlation to within about ±1 %, which is the stated uncertainty of the correlation for the saturated liquid. At higher temperatures, the deviations are somewhat dependent upon pressure and span the interval (-3 to -6) %.…”
Section: Correlation Of the Viscosity Ratios At Low Temperatures Thsupporting
confidence: 90%
“…The critical parameters are consistent with the equation of state. We obtained the coefficients in Table 3 by fitting the liquid-phase viscosity data of several sources (42)(43)(44)(45)(46)(47)(48) at pressures up to 50 MPa, the upper limit of the equation of state. The reference fluid was n-dodecane.…”
Section: 3mentioning
confidence: 99%
“…Gas-phase viscosity data were unavailable, so the method of Chung et al (20) was used to estimate LJ parameters. Liquid-phase viscosity data from three sources (43)(44)(45) were used to determine the coefficients in Table 3 (these sources also were used for 1-methylnaphthalene), with n-dodecane as a reference fluid. The deviations are given in Figure 8.…”
Section: Tetralin (Tetrahydronaphthalene)mentioning
confidence: 99%
“…Since the volume is equal to the mass of fluid added to the cell divided by the calculated density, the primary error in the volume calibration curve emanates from the error in the calculated density. This is a maximum of 0.50% of the density at high pressures determined from the NIST Chemistry WebBook for trimethylpentane and n-decane [7], and much less than 0.50% for the trimethylpentane data of Malhotra [5] and the n-decane data of Caudwell [6]. The maximum estimated error of the NIST data is used to determine the accumulated error of the technique used in the present study.…”
Section: Calibration Of Cell Volume For Density Measurementsmentioning
confidence: 99%
“…Connected to the piston is a rod with a magnetic end piece, called a core, and as the piston moves the magnetic core travels through the LVDT located outside the high-temperature air bath. The view cell volume is calibrated using highly accurate trimethylpentane at 50°C [5], n-decane at 150°C [6], and ndecane at 250°C [7] data. Typically, 7.0 to 9.0 ± 0.001 grams of the fluid of interest are charged to the view cell, which results in an uncertainty of not more than 0.20%.…”
Section: Calibration Of Cell Volume For Density Measurementsmentioning
confidence: 99%